Review of the Granting of Cultivation Rights on Land Management Rights Based on Positive Law - Setiawan, Muhammad Rifaldi; Anugerahayu, Ayang Afira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study is a normative investigation that seeks to evaluate the review process associated with the allocation of HGU on HPL land. This regulation stands in contradiction to the UUPA, which stipulates that HGU should only be assigned on state-owned land; however, the legitimacy of the recent regulations offers a pathway for granting HGU on HPL territory. Additionally, this paper employs both the statutory approach and the conceptual approach. Legally speaking, the UUPA does not recognize HPL as a